ASSESSING THE RELATIONSHIP BETWEEN MATERIALISM AND CONSPICUOUS CONSUMPTION: VALIDATION IN THE INDIAN CONTEXT - Pearly Saira Chacko; Sanjeev Prashar; Hareesh N. Ramanathan (Asian Academy of Management Journal, 2018)
With urbanisation and increase in per capita income, there has been an astonishing rise in material-oriented tendencies in the Indian population. This study aims to examine the significance of material-centric behaviour of women in today’s growing consumer societies. Using structural equation modelling, the paper proposes a model depicting the relationship between materialism and conspicuous consumption among Indian women consumers. Though all the three factors, namely success, centrality, and happiness, contribute to materialism that has a positive influence on conspicuous consumption, the unique finding of the study is the prominence of centrality over the other two predictors among Indian female shoppers.